[tex]\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^{-n} \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^{-n}} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^{-m}\implies a^{n-m} \\\\\\ ~\hspace{7em}\textit{rational exponents} \\\\ a^{\frac{ n}{ m}} \implies \sqrt[ m]{a^ n} ~\hspace{10em} a^{-\frac{ n}{ m}} \implies \cfrac{1}{a^{\frac{ n}{ m}}} \implies \cfrac{1}{\sqrt[ m]{a^ n}} \\\\[-0.35em] \rule{34em}{0.25pt}[/tex]
[tex]\bf \left( \cfrac{4^{\frac{5}{4}}\cdot 4^{\frac{1}{4}}}{4^{\frac{1}{2}}} \right)^{\frac{1}{2}}\implies \left( \cfrac{4^{\frac{5}{4}\cdot \frac{1}{2}}\cdot 4^{\frac{1}{4}\cdot \frac{1}{2}}}{4^{\frac{1}{2}\cdot \frac{1}{2}}} \right)\implies \cfrac{4^{\frac{5}{8}}\cdot 4^{\frac{1}{8}}}{4^{\frac{1}{4}}}\implies \cfrac{4^{\frac{5}{8}+\frac{1}{8}}}{4^{\frac{1}{4}}}[/tex]
[tex]\bf \cfrac{4^{\frac{6}{8}}}{4^{\frac{1}{4}}}\implies \cfrac{4^{\frac{3}{4}}}{4^{\frac{1}{4}}}\implies 4^{\frac{3}{4}}\cdot 4^{-\frac{1}{4}}\implies 4^{\frac{3}{4}-\frac{1}{4}}\implies 4^{\frac{2}{4}}\implies 4^{\frac{1}{2}}\implies \sqrt{4}\implies 2[/tex]